Pengelolaan Kesenian Dayakan Desa Kebondalem Bejen Temanggung Sebagai Bagian Dari Upaya Revitalisasi Kesenian Tradisional - Laura Andri Retno Martini (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2018)
Traditional art is used to express a sense of beauty from within the human soul. As part of culture, traditional art has messages in the form of knowledge, ideas, beliefs and norm values. One example of traditional art is Dayakan. Dayakan is a dance-shaped art owned by the people of Kebondalem Village, Bejen District, Temanggung Regency, Central Java. Through a qualitative descriptive approach with observation and literature techniques, it was found that in order to overcome the expansion of global art and culture, efforts were needed to manage Dayakan arts in order to improve and preserve regional art and culture in the midst of changing times and increasingly intense foreign cultural influences in Indonesia.